Outdoor learning in early childhood education: exploring benefits and challenges - Kiviranta Leena; Lindfors Eila; Rönkkö Marja-Leena; Luukka Emilia (Routledge, Taylor & Francis Group, 2025)
Background: Studies indicate that access to nature may increase general human health and wellbeing. As a learning environment, the outdoors can also positively influence children’s personal and social growth, healthy development, wellbeing and learning abilities. To maximise the potential offered by outdoor learning, it is necessary to gain deeper understanding of its implementation, particularly in early childhood education and care (ECEC) settings.
Purpose: This review study sought to explore a small subset of relevant literature in detail, in order to identify and describe the noted benefits and challenges of implementing outdoor learning in early childhood.
Method: A narrative synthesis was undertaken. In total, 20 studies from 10 different countries on learning outdoors during ECEC were selected for in-depth analysis and synthesis. The benefits and challenges of outdoor learning implementation in ECEC were identified and categorised using thematic analysis.
Findings: The analysis yielded a detailed description of the opportunities, preconditions and resources for outdoor learning. Six data-driven categories emerged (i) children’s holistic development; (ii) health and wellbeing; (iii) multimodal, hands-on learning opportunities; (iv) experiences in and of nature; (v) teachers as mediators; and (vi) the organisation of outdoor learning. Overall, these categories suggested that three main elements need to be considered when planning and implementing outdoor learning: as well as providing experiences in and of nature for children, outdoor learning may benefit the holistic wellbeing and well-rounded development of children and can offer multimodal, hands-on learning opportunities. According to the analysis, one of the main challenges related to teachers’ understanding and knowledge around organising and implementing outdoor learning opportunities for young children.
Conclusion: In addition to highlighting the compelling potential benefits of outdoor learning in ECEC, the study findings draw attention to the need for teachers to be supported in developing the required competences to implement outdoor learning. In particular, introducing multimodal outdoor learning into educational practice necessitates pre- and in-service teacher education and professional development.